Clinico-epidemological profile of migraine and its correlation with depression, anxiety and stress in a teritiary care hospital in South India - Renuji, Baishyak; Pillai, Rammohan Krishna (Nepal Journal of Neuroscience, 2023)
Introduction: We studied the clinico-epidemiological profile of patients with migraine and to study the correlation of migraine severity with depression, anxiety and stress. Materials and Methods: 98 subjects who were meeting inclusion and exclusion criteria were studied after obtaining informed written consent. Data was collected using prestructured performa and then analysed using SPSS software. Result: 64.3% patients had unilateral headache and 76.5% had frontal area pain. Migraine with aura was present in 40.8% with commonest aura being visual (85%). Most common visual aura was scotoma (47.5%) and the most common associated symptom was photophobia (83.7%) followed by nausea (78.6%). The most common trigger was sun exposure (70.4%) followed by sleep deprivation (69.4%). Severe disability was present in 26.5% of subjects. Severity of migraine showed significant positive association with those who were taking alternative medicine. Migraine severity showed positive correlation with depression, anxiety and stress with correlation coefficient of 0.506, 0.509, and 0.604 respectively. Maximum correlation was with stress which may be considered as an independent risk factor for severe migraine. Conclusion: Anxiety, depression and stress were strongly associated with severe migraine. They can act as factors that trigger and perpetuate migraine, of which stress may be considered as an independent risk factor for severe migraine. Early screening and management of depression, anxiety and stress might provide better control of migraine, thus improving the quality of life of migraineurs.